Decreasing prevalence and stagnating incidence of Hepatitis C‐co‐infection among a cohort of HIV‐1‐positive patients, with a majority of men who have sex with men, in Germany, 1996–2019. Issue 6 (31st March 2022) - Krings, Amrei; Schmidt, Daniel; Meixenberger, Karolin; Bannert, Norbert; Münstermann, Dieter; Tiemann, Carsten; Kollan, Christian; Gunsenheimer‐Bartmeyer, Barbara
Abstract: Co‐infection with Hepatitis C virus (HCV) among HIV‐positive patients leads to accelerated progression of liver disease and AIDS. Due to increased HCV prevalence and incidence, co‐infection requires monitoring trends among HIV‐positive individuals. This will help target prevention strategies and support to reach the global goals of eliminating viral hepatitis as a public health threat. In this analysis HCV prevalence and incidence were determined for the years 1996–2019 from yearly blood samples and questionnaire details among HIV‐1‐positive patients, with a majority of men who have sex with men, belonging to a nationwide, multicentre observational, prospective cohort study. The results show that HCV prevalence for acute/chronic and resolved infection increased until 2014 to 12%. Since then, prevalence of acute/chronic HCV infection rapidly decreased and prevalence of resolved infections showed a steady increase. HCV incidence was highest in 2010 and lowest in 2017; however, no significant change in HCV incidence could be seen over the years. Therefore, the introduction of directly‐acting antiviral agents for HCV treatment notably decreased prevalence and potentially incidence of acute/chronic HCV infection. Nevertheless, prevalence and incidence of HCV among these HIV‐1‐positive study participants remain high compared with the general population and justify the need for continuous HCV prevention and treatment efforts among HIV‐positive individuals.